Trauma-informed care in social work education implications for students, educators, pedagogy, and field - Dylan, Arielle; Tufford, Lea (New York Routledge, 2025)
"Structured and informed by social justice orientations, this essential volume explores how trauma-informed care can be integrated in all aspects of social work education. This handbook incorporates a critical and ecologically focused lens with an emphasis on resilience, healing, and strengths-based approaches. With contributions from over sixty experts in the field of social work, education, psychology, and counselling, this comprehensive book provides current understandings of how trauma manifests in the lived experience of social work students. The book begins by introducing why trauma-informed care is needed in social work and addresses the reality of historical trauma. Each chapter views the social work student at the center of the educational journey and considers how trauma can shape experiences in various settings such as the classroom, curriculum, field, educational policy and community involvement, and support services. Chapters cover topics such as the neuroscience of trauma, poverty, disability, racism, experiential approaches, online course delivery, climate change, mindfulness, student mental wellbeing, and more. This handbook is a must-read for social work educators and field instructors who seek to prevent and minimize trauma in their social work pedagogy. It is also beneficial for undergraduate and graduate courses such as child and youth care, addiction services, and foundations of social work"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Psychic trauma; Social work education